Common Mistakes in Diagnosis of Ankle and Foot Injuries - Anderson, Mark W.; Kresse, Maxine E. (Seminars in Musculoskeletal Radiology, 2025)
Ankle and foot injuries are extremely common among athletes and nonathletes alike. Clinical findings are often nonspecific, and many injuries are difficult to diagnose with imaging, even using advanced techniques, and a delay in diagnosis may have significant adverse long-term consequences. Thus it is important to be familiar with the location and imaging appearances of these injuries. This article addresses several injuries that are commonly missed when imaging the ankle and foot.
Keywords: ankle and foot; syndesmosis; navicular; Lisfranc; plantar plate